Political Participation of Women in Panchayat Raj Insitution: A Sociological Study in Kalinga Village, Bhiwani: Examining the Influences on Women's Political Participation in Panchayat Raj Institutions (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Women constituting around a half of population in India. Without contribution of women, there is impossible the whole development of the country. This half population of India is engaged in the activities of household. The whole growth of India is possible when women should contribute in social, economic, cultural and political arena of the country. To improve the political participation of women, 73rd amendment in constitution has given reservation of one third of total seats in local self-governance. Today,women are having a 50 reservation in the Panchayati Raj Institutions (Local Self Governance). Giving this constitutional right to women is to increase the political participation of women in local government especially in decision making and play a role in development in the country. Constitution provided the rights to women, but these rights are seen on paper only. There is arise many question like the women enjoying these constitutional rights or somebody else using these rights. That’s why the present study has made to know the how much relatives’ influences in political career of women representatives and to assess the performance of women representatives in Panchayat Raj System. The present study has been conducted in Village Kalinga in district Bhawani, Haryana. There are primary and secondary data were collected from different sources. The primary data has been collected by using interview schedule. This study has been conducted on 21 samples from Grampanchayat. The random sampling technique was adopted to select samples. In this paper argues that still the women representatives in Panchayati Raj Institutions were influenced by the family member. The political decisions have been taken by the other family members. It is important to know the problem regarding to their performance then only we can find the remedy for the same.